2012
DOI: 10.1155/2012/308097
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychiatric Symptoms in Parkinson's Disease with Mild Cognitive Impairment and Dementia

Abstract: Neuropsychiatric symptoms commonly complicate Parkinson's disease (PD), however the presence of such symptoms in mild cognitive impairment (PD-MCI) specifically has not yet been well described. The objective of this study was to examine and compare the prevalence and profile of neuropsychiatric symptoms in patients with PD-MCI (n = 48) to those with PD and no cognitive impairment (PD-NC, n = 54) and to those with dementia in PD (PDD, n = 25). PD-MCI and PDD were defined using specific consensus criteria, and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 40 publications
5
50
0
Order By: Relevance
“…In this study, apathy was also significantly correlated with factors such as advanced stage of disease and dopamine agonist load and all cognitive measures used in that study (e.g. Trail Making Test, Verbal Fluency Task, Wisconsin Card Sorting Test, 5-minute recall of 3 words and MMSE) [16].…”
Section: Apathysupporting
confidence: 54%
See 2 more Smart Citations
“…In this study, apathy was also significantly correlated with factors such as advanced stage of disease and dopamine agonist load and all cognitive measures used in that study (e.g. Trail Making Test, Verbal Fluency Task, Wisconsin Card Sorting Test, 5-minute recall of 3 words and MMSE) [16].…”
Section: Apathysupporting
confidence: 54%
“…In PD patients with dementia the prevalence of neuropsychiatric symptoms was found to be higher. In the Aarsland et al study, 50 out of 139 patients were demented [14] and in a further study, Leroi et al [16] reported that 96% of PD patients with dementia presented with at least one neuropsychiatric symptom. Another study demonstrated an association between the total Neuropsychiatric Inventory (NPI) score [17] and depression and anxiety (as measured by the Hospital Anxiety and Depression Scale) [18] in non-demented PD patients.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…A study of the prevalence of psychosis in PD in those without any cognitive impairment, as compared to those with mild cognitive impairment or dementia, demonstrated that psychotic symptoms positively correlated with severity of cognitive impairment; 20 this was also found in the PRIAMO trial. 16 In attempts to develop specific criteria for psychotic symptoms without confounding cognitive impairment, 250 patients with idiopathic PD and mini-mental status examination (MMSE) .23 from community-based clinics were evaluated for psychotic symptoms based on National Institute of Neurological Disorders and Stroke/National Institute of Mental Health criteria.…”
Section: Cognitive Impairmentmentioning
confidence: 86%
“…17,[44][45][46] These broad reported ranges highlight the difficulty of carrying out cross-study comparisons. Common variations in study design identified from a targeted literature review (unpublished findings) include the criteria for patient selection, the definition of PDP, the symptoms of psychosis that were of interest to study investigators, differences in the methodology used to assess symptoms, and the timeframe over which symptoms were observed.…”
Section: Disruptiveness and Comorbidity Ratesmentioning
confidence: 99%